Socio-Political Construction of Tribe and Representation of Legitimate Mechanisms of Power: Case Study of Qashqai Tribe - A. Nazari; M. Yazdanpanah (Taḥqīqāt-i Farhangī-i Īrān)
The nomadic structure of the Qashqai tribe has an ancient history that has continued for nomadic life. The system had its own administrative political organization, which was shaped by nomadic living conditions and nomadic. At the head of this tribal system, there was a monk named Ilkhani, from the beginning of the formation of the Qashqai tribe, from the time of the Safavids, in the hands of a family called Shahilo. The main question of the present article is that what was the social political structure in Qashqai and how has the legitimizing mechanisms been implemented? The hypothesis of the article is that the social structure of the Qashqai tribe has been hierarchically in response to the needs of the tribe, and the structure of power in it is not necessarily based on the violence of the rulers of the tribe, but based on symbols, rituals and customs was in tribe. Therefore, the distinction between current research and this paper based on the theoretical framework of violence or symbolic domination, we study of the mechanisms and components of the legitimacy of the power of the leaders and attempt to study the subject from the perspective of historical sociology.